Unravelling the detrimental effect of water in the polyol synthesis of ultrathin silver nanowires. Issue 35 (25th July 2019) - Chen, Guinan; Wang, Guixin; Gu, Yujia; Wu, Zelei; Ye, Changhui
Abstract : Generation of particle by-products during the synthesis of ultrathin silver nanowires can be suppressed via eliminating water in a precursor mixing step. Abstract : In the synthesis processes of ultrathin silver nanowires, it has often been found that a large amount of particles coexist with nanowires, in sharp contrast to the phenomena observed in the synthesis of thicker silver nanowires. The reason for producing such a large amount of particle by-products is not well understood. Herein, we show that water plays a critical role in the initial stage of the formation of Ag(Cl, Br) particles during the mixing of precursors prior to the nucleation of silver seeds. When a small volume of water is deliberately added to the ethylene glycol solvent during the mixing of the precursors, the Ag(Cl, Br) particles exhibit a bimodal diameter distribution and the size of the particles does not favor the nucleation and growth of ultrathin silver nanowires. The elimination of water from ethylene glycol during the mixing of precursors results in size focusing of Ag(Cl, Br) particles to a range that is effective in directing the nucleation and growth of ultrathin silver nanowires. The amount of particle by-products can be significantly reduced, dramatically simplifying the purification process of the raw product of ultrathin silver nanowires after synthesis.